Multi-Layer Human-Robot Teaming: From Earth to Space. Issue 19 (2019) - Drepper, A.; Baltzer, M.; Cowley, A.; Flemisch, F.O.
Abstract: Robotic assistants will play an important role in future space exploration activities. In order to provide an optimal human-robot cooperation and interaction, the interface between user and machine requires an intuitive design. In this paper an interface evaluation methodology is presented as the synthesis of existing approaches in space projects and general recommendations by Human Factors Engineering. The MARVIN project of the European Space Agency (ESA) serves as a test case for this methodology. As a subsequent step to the evaluation results, the relevance of design improvements is derived from specific guidelines for robotics and from experiences in Earth exploration systems with humans involved.